STYLISTIC AND PRAGMATIC FUNCTIONS OF THIRD-PERSON PRONOUNS: A CROSS-GENRE COMPARATIVE ANALYSIS IN FIVE LANGUAGES - Pazilova Nasibaxon Muxammadkasimovna (Modern American Journals, 2025)
This paper explores the stylistic and pragmatic functions of third-person personal pronouns across five structurally distinct languages: Uzbek, English, Russian, Arabic, and Persian. Drawing from literary, political, and religious genres, the study analyzes how pronouns encode degrees of formality, respect, gender, and social distance. It highlights how the speaker–referent relationship is linguistically mediated within different cultural and discursive contexts. The comparative approach offers theoretical and practical insights for linguists, translators, and intercultural communication scholars, emphasizing the cultural and pragmatic weight carried by pronouns in multilingual texts.
Keywords: Third-person pronouns, stylistic pragmatics, intercultural communication, discourse genres, politeness strategies, gender neutrality